PRIORITY AREAS FOR THE EFFECTIVE DEVELOPMENT OF BEEF CATTLE BREEDING - Okutaeva Saule Tolegenovna,; Mukhambetova Zamira Seydahmetovna,; Tolysbaeva Marzhan Sovetbekovna,; Narbaeva Gulmira Kuanyshevna, (Academic Journal of Physical and Chemical Sciences, 2020)
Sustainable and efficient meat production is possible through the development of integration ties designed to improve the system of intersectoral interaction and exchange. It should be noted that the methodological foundations of these processes are the same for social production, but at the same time, they acquire special features in beef cattle breeding due to the specifics of the industry and the complexity of managing structurally interconnected structural elements that make up integrated formations. The need to increase the efficiency of domestic livestock for accelerated import substitution in the country's agri-food market involves the development of additional measures to increase the intensity and effectiveness of local innovation. In this situation, the main condition for the profitable work of livestock enterprises is intensive industry management with the development of innovative resource-saving technologies for keeping and feeding animals, modern breeding methods that provide high productivity, preservation and conversion of feed, organization of deep processing of products, etc.